Reclamation of tidal flats and shorebird declines in Saemangeum and elsewhere in the Republic of Korea. (1st June 2016) - Moores, Nial; Rogers, Danny I.; Rogers, Ken; Hansbro, Philip M.
Abstract: Saemangeum, in the Republic of Korea (ROK, commonly called South Korea) was one of the most important shorebird staging sites in the Yellow Sea. It supported at least 330 000 shorebirds annually between 1997 and 2001, including ∼30% of the world population of Great Knots ( Calidris tenuirostris ) during both northward and southward migration. Construction of a 33-km long sea-wall was completed in April 2006. We show that shorebird numbers at Saemangeum and two adjacent wetlands decreased by 130 000 during northward migration in the next two years and that all species have declined at Saemangeum since completion of the sea-wall. Great Knots were among the most rapidly affected species. Fewer than 5000 shorebirds were recorded at Saemangeum during northward migration in 2014. We found no evidence to suggest that most shorebirds of any species displaced from Saemangeum successfully relocated to other sites in the ROK. Instead, by 2011–13 nearly all species had declined substantially in the ROK since previous national surveys in 1998 and 2008, especially at more heavily reclaimed sites. It is likely that these declines were driven by increased mortality rather than movement to alternate staging sites given that other studies have shown concurrent declines in numbers and survival on the non-breeding grounds. This is the first study in the East Asian—Australasian Flyway to confirm declines of shorebirds at a range of geographical scales following a single reclamation project. The results indicate that if migratory shorebirds are displaced from major staging sites by reclamation they are probably unable to relocate successfully to alternate sites.